Segurança da informação: uma abordagem sobre proteção da privacidade em internet das coisas - Machado Junior, Dorival Moreira (2018)
The concept of Internet of Things (IoT) refers to a network of objects capable of generating, collecting, and exchanging data between them. This interconnection of intelligent objects tends to provide improvements in the well-being of people so that the more “things” acquiring or generating data, the better may be the result propitiated by IoT. On the other side, privacy is best guarded in the face of the minimum supply of data or personal information. They are contrary paths that characterize a paradox. With this, studies are needed that point out possibilities that favor the growth of IoT and at the same time do not let privacy be totally succumbed to technological evolution. The user permeates both factors, being situated in the center. This paradox as well as the lack of documentation and standardization in terms of privacy protection in IoT becomes the research problem. The hypothesis suggests the need for a standard that allows such protection. The scope of standardization of the Internet is very extensive, it is necessary to determine the limits of performance of this thesis. For this, the mapping of the mechanism by which the rules and standards of the Internet are established, as well as defining a standard scenario of IoT applicable in any environment in which it is inserted. Once these parameters were established, it was possible to continue through a critical exploratory analysis of the context that is considered emerging mainly by the lack of documentation regarding the protection of privacy in IoT. As a result, a directing to privacy protection in IoT was systematized. This has as characteristics: to be applicable specifically to the IoT environment; Have as basic principles consider all user data as private as well as adopt a restrictive policy. It is also characterized by a step of human validation, in which it is required that the user allows the sharing of their data, as well as establish the trust to the device to link, that is, the destination of the data. In this way, the user is instigated to have science of their data in question beyond the destination of these. At the end, the conclusion is made by analyzing the security objectives of other models justifying the contrary or favorable opinion for application in IoT